The labors of Hercules Beal - Schmidt, Gary D. (Clarion Books, an imprint of HarperCollins Publishers, 2023)
"Herc Beal knows who he's named after--a mythical hero--but he's no superhero. He's the smallest kid in his class. So when his homeroom teacher at his new middle school gives him the assignment of duplicating the mythical Hercules's amazing feats in real life, he's skeptical. After all, there are no Nemean Lions on Cape Cod, and not a single Hydra in sight. Missing his parents terribly and wishing his older brother wasn't working all the time, Herc figures out how to take his first steps along the road that the great Hercules himself once walked. Soon new friends, human and animal, are helping him. And though his mythical role model performed his twelve labors by himself, Herc begins to see that he may not have to go it alone."--Page 2 of cover.